Framing of Water Crisis in Bandung on Pikiran Rakyat Online - Rahmat Hidayat , Dadang; Aunillah Sirait, Rinda (International Journal of Psychosocial Rehabilitation, 2020)
Cities in Indonesia have been facing water crisis, particularly water scarcity and poor use of water. The media should play an important role in preserving water resources and encouraging good use of water. Using Robert M. Entman’s framing approach, this study seeks to describe how media, particularly Pikiran Rakyat Online of Bandung, construct water crisis. The results showed that water crisis has not been a significant issue due to the low frequency of coverage. And although the media has constructed it perfectly, it is not strong enough to show a positive construct of moral values and recommended solutions for water conservation. The only strong aspect is the way the media delivers the surface condition, i.e. problem identification and the cause of the problems at a glance.